Happy seeder – A game changer technology - Suryavanshi, Priyanka; Sharma, Munish; Singh, Y V (Indian Farming, 2022)
Paddy is the most important kharif crop of Punjab which produces more than 20 million tonnes of biomass. There is a very narrow window for sowing of succeeding wheat crop. Consequently, farmers burn the paddy residue in the field itself which causes serious environmental problems and adversely affects soil health. Therefore, paddy straw management is a burning problem and needs to be tackled. Happy seeder provides an economically viable alternative to residue burning. It allows farmers to sow wheat immediately after their paddy is harvested without burning paddy residue for land preparation.